Design and application of polyurea microcapsules containing herbicide (oxyfluorfen). Issue 1 (1st January 2020) - Rao, Jayprakash; Chandrani, Amar Nath; Powar, Anil; Chandra, Sudeshna
ABSTRACT: Polyurea, a controlled release material, has been widely applied in agricultural fields due to high thermal stability and low cost. In this article oxyfluorfen polyurea microcapsules suspension was successfully prepared by interfacial polymerization using diisocyanate and polyamines such as Ethylenediamine, Hexamethylenediamine, Diethylenetriamine in presence of green solvent, i.e., N, N-dimethyldecanamide. The microcapsule suspension of oxyfluorfen has not been researched yet by using solvent N, N-dimethyldecanamide and polyamines. The effect and the type of diamines on the morphology and properties of the microcapsules have been investigated. The synthesized microcapsules were characterized by scanning electron microscope, ultraviolet spectrometry, Fourier transform iInfrared spectrometer, thermogravimetric analysis and particle size analyser. The effect of the core to shell ratio on encapsulation efficiency and release kinetics were also studied. The oxyfluorfen microcapsules had an excellent encapsulation efficiency (98.2%) using EDA as the monomer and Release kinetics depended upon the type of monomers used and also on core to shell ratio used (6.5:1, 5:1, 4:1). As core to shell ratio was increased the encapsulation efficiency was found to decrease. Prepared Microcapsules when sprayed on paddy crop was found to be safe in comparison with Emulsifiable concentrate sample.